Manejo Geral dos Suínos- IFTO/Araguatins. - Fernandes, Rafaela Silva (Universidade Federal do Tocantins, 2023)
This report describes the activities carried out during the Supervised Internship of the Federal University of Tocantins at the Federal Institute of Tocantins (IFTO) in the swine sector, based in the municipality of Araguatins - TO, during the period of 28 March 2019 to June 7, 2019, totaling 360 hours, and had as purpose to allow the monitoring of the activities developed in the sector. The internship was supervised by Professor Dr. Afonso Siqueira Dimpério.